Exporting and FDI with endogenous productivity - Oana Secrieru; Marianne Vigneault (Bank of Canada, 2007)
This paper provides an analysis of how a firm's decision to serve a foreign market by exporting or by engaging in foreign direct investment (FDI) affects firm productivity, when productivity is endogeneous as a function of training. The main result of our paper is that, with endogeneous productivity, exporting results in lower productivity than does FDI, but exporting may result in higher or lower employment and output than does FDI. We also show that FDI has lower employment, higher training, higher wages and higher productivity than does production for the home market. A further interesting and unexpected result of our model is that exporting results in the same level of training and productivity as does production for the home market. However, under the same demand conditions, the exporting firm employs less labour for foreign production than for home production and, consequently, output for the foreign market is lower than output for the home market. In addition, we investigate the firm's decision to serve the foreign market by exporting or by engaging in FDI and determine parameter values for which either regime is chosen.
Keywords: F22; F23; 330; International topics; Labour markets; Productivity; Strategisches Management; Direktinvestition; Export; Produktivität; Beschäftigungseffekt; Wirtschaftsmodell